Synthesis, characterization and antibacterial studies of Mn(II) and Co(II) complexes of an ionic liquid tagged Schiff base - Saha Sanjoy; Das Ananya; Acharjee Kaushik; Sinha Biswajit (Journal of the Serbian Chemical Society, 2016)
Mn(II) and Co(II) complexes of an ionic liquid-based Schiff base, 1-{2-(2-hydroxybenzylideneamino)ethyl}-3-methylimidazolium bromide, were synthesized and characterized by various analytical and spectroscopic methods such as elemental analysis, UV-Visible, FT-IR, 1H NMR, ESI-MS and magnetic susceptibility measurement. These studies indicated tetrahedral geometry for the complexes. The Schiff base ligand and its complexes were tested for in vitro antibacterial activities to assess their inhibiting potentials against Escherichia coli and Lactobacillus sp.